RUANG PUBLIK ADAPTIF PLUIT SEBAGAI RESPONS TERHADAP KESENJANGAN SOSIAL-EKONOMI DI KAWASAN PLUIT, JAKARTA UTARA - Atsuhiro Kubo; Maria Veronica Gandha (Jurusan Arsitektur dan Perencanaan, 2021)
Gated communities in Jakarta had increased in numbers ever since the incident of 1998 riots. The Idea that was meant to create a better community carried out side-effects that highlighted the differences in terms of races and class. It led to a formation of a divided society where people would be less likely to interact with the other groups. The upper middle class chinese is one that has grown colder toward the larger society. This can be seen clearly in how the height of fences in local houses has kept increasing up until now. They rarely use public spaces where people from different backgrounds are present. And as long as public buildings come as an intervention from the outside world, this group will remain untouched. The Adaptive Public Space in Pluit is based on an idea called